Highly sensitive persons (HSPs) and the situation of foreign language testing - Nosidlak Katarzyna (Psychology of Language and Communication)
We carried out a preliminary study exploring the influence of sensory processing sensitivity (SPS) on the situation of foreign language testing. Initially, SPS levels were determined for 103 English philology students. Then, the participants reported their perceived stress levels during language tests and their preferences for test form (onsite vs. online) and type (written vs. oral). Subsequently, 50 students completed a written interview, expressing their opinions on factors that, beyond their knowledge and skills, had influenced their test performance. The data analysis indicated that oral language exams were generally perceived as more stressful by all participants, regardless of their SPS levels. Regarding test type and form preferences, no statistically significant differences were found between the three distinguished groups. In turn, thematic analysis of the written interviews suggests that, in testing situations, highly sensitive students reported to be especially affected by sensory disruptors.